2009
DOI: 10.1111/j.1582-4934.2009.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factors in stem cells and cancer

Abstract: Cellular properties are influenced by complex factors inherent to their microenvironments. While oxygen deprivation (hypoxia) occurs in tumours because of rapid cell proliferation and aberrant blood vessel formation, embryonic cells develop in a naturally occurring hypoxic environment. Cells respond to hypoxia by stabilizing hypoxia-inducible factors (HIFs), which are traditionally viewed to function by altering cellular metabolism and blood vessel architecture. Recently, HIFs have been shown to modulate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 103 publications
1
86
0
Order By: Relevance
“…30 This finding is of particular importance, as both normal and tumor stem cells are in vivo harbored in an oxygen poor environment. 37 Previous data reported that RA reduces breast CSC population, while inducing differentiation. 17 Our data show that, among the NRs agonists tested, the RXR agonist IIF is the most active molecule in inhibiting the pro-inflammatory NF-kB/IL6 pathway and in inducing the expression of differentiation markers (KRT18 and ERa) in breast CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…30 This finding is of particular importance, as both normal and tumor stem cells are in vivo harbored in an oxygen poor environment. 37 Previous data reported that RA reduces breast CSC population, while inducing differentiation. 17 Our data show that, among the NRs agonists tested, the RXR agonist IIF is the most active molecule in inhibiting the pro-inflammatory NF-kB/IL6 pathway and in inducing the expression of differentiation markers (KRT18 and ERa) in breast CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-2 ␣, but not HIF-1␣, is a direct upstream regulator of Oct-4 and binds to specific HREs within the promoter of murine Oct-4. 51,56 HIF-1␣ can also directly interact with ␤-catenin and with Notch1. 56 A first clue of the link between Notch and hypoxia derives from studies demonstrating that the Notch target gene Hes1 was up-regulated by hypoxia in neuroblastoma cell lines.…”
Section: Hypoxia and Hif-1␣mentioning
confidence: 99%
“…51,56 HIF-1␣ can also directly interact with ␤-catenin and with Notch1. 56 A first clue of the link between Notch and hypoxia derives from studies demonstrating that the Notch target gene Hes1 was up-regulated by hypoxia in neuroblastoma cell lines. 57 56 Some of these genes contain both HRE-and CSL-binding sites, suggesting that hypoxia and Notch may have additive effects on transcription.…”
Section: Hypoxia and Hif-1␣mentioning
confidence: 99%
“…This stress can occur during embryonic development, where crowding and rapid cell division causes a shortage of blood and oxygen supply (Keith and Simon 2007;Mazumdar et al 2009). Hypoxia can also be brought on by impaired blood flow due to heart attack or stroke (Semenza 2014a;Ferdinand and Roffe 2016).…”
Section: Introductionmentioning
confidence: 99%